Correlation of Intra-Operative Frozen Section Consultation With the Final Diagnosis At a Tertiary Referral Center in Dhaka - Khaled, A; Agrawal, L; Nasir, TA (Pulse, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/pulse.v5i2.20261 Pulse Vol.5 July 2011 p.22-25